Разведение зебр в Аскании-Нова - Треус, В.Д.; Лобанов, Н.В. (Вестник зоологии, 1970)
Рассматриваются систематика, численность и распространение трех видов зебр Юго-Восточной Африки. В зоопарке «Аскания-Нова» содержатся зебры Греви, Гартмана, Гранта и Чапмана. The taxonomy, quantity and distribution of three species of zebra from the SouthEastern Africa are considered. At the zoo «Askaniya-Nova» there are Equus grevyi, E. zebra hartmannae, E. burchelli antiquorum and E.b. boehmi.
The experiments on breeding E. burchelli in Askaniya-Nova are the most demonstrative, For the period of 1914—1968 the progeny increases by 78 individuals. The terms of reproduction and pregnancy, life duration and dimensions and weight of animals are presented.